Law and Politics in Alain Renault - Ntolas, Nikolaos (Conatus - Journal of Philosophy, 2017)
This study focuses on the relation between law and good. It examines whether the concept of “good” in a society has preceded the establishment of the state or not. This is an issue that concerns the way of integrating law into the way of conceiving the fair and just order. Within this frame, Renaut regarded as an oversimplification the division between liberalism and socialism, which has been formed since the 19th century. What is essential for Renaut is how liberalism and socialism should deal with the transition from a fair authority to a fair society, which is basically an issue of resource allocation. Renaut maintains that what is common between liberalism and socialism is the end of the state, though by different means. In fact, apart from the traditional dispute, Renaut also analyses the most recent one between liberalism and republicanism. In this case, he favors the liberal model, because it allows for more deliberation and argumentation. Moreover, Renaut is concerned about the post-modern situation in politics, whose main characteristics are the deconstruction of power and the weakened role of politicians, who are just aiding towards the imposition of certain hierarchies.